2021
DOI: 10.1136/bmjopen-2021-051769
|View full text |Cite
|
Sign up to set email alerts
|

Facilitators and barriers to using telepresence robots in aged care settings: a scoping review protocol

Abstract: IntroductionSocial isolation is a significant issue in aged care settings (eg, long-term care (LTC) and hospital) and is associated with adverse outcomes such as reduced well-being and loneliness. Loneliness is linked with depression, anxiety, cognitive decline, weakened immune system, poor physical health, poor quality of life and mortality. The use of robotic assistance may help mitigate social isolation and loneliness. Although telepresence robots have been used in healthcare settings, a comprehensive revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“… 16 The objective, inclusion criteria and method for this scoping review were specified in advance and documented in a protocol. 17 The electronic search strategy and details for the search process and search terms, including the adjacency (ADJn) operator and truncation used in the search, have been reported in the published protocol.…”
Section: Methodsmentioning
confidence: 99%
“… 16 The objective, inclusion criteria and method for this scoping review were specified in advance and documented in a protocol. 17 The electronic search strategy and details for the search process and search terms, including the adjacency (ADJn) operator and truncation used in the search, have been reported in the published protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Since the beginning of the COVID-19 health crisis, different stakeholders have shown an increasing interest in innovative remote communication solutions and TRs [25][26][27][28][29][30][31][32][33][34][35][36][37][38]. However, thus far, there is limited available evidence concerning the implementation and usefulness of TRs in a home-dwelling OA population.…”
Section: Trs: a Solution That Has Not Been Thoroughly Studied For Sen...mentioning
confidence: 99%
“…31 35 36 39 40 45 47-49 52 53 The scoping reviews also focused on the classification and mechanisms of action of digital interventions. [29][30][31][32][33][34][35][36][37][38] Although most reviews found the effectiveness of digital interventions, most digital intervention techniques are not tailored for older adults. 40 55 56 The 'heterogeneity' of older adults, such as declining cognitive and sensory abilities, can make them face barriers that do not easily allow them to use digital technologies.…”
Section: Open Accessmentioning
confidence: 99%
“…We systematically searched the PubMed database for current literatures without language or year restrictions, using the terms ‘loneliness’, ‘older adults’, ‘intervention’ and ‘systematic review’. We identified 28 reviews of digital interventions, including 10 scoping reviews,29–3811 systematic reviews (including 7 meta-reviews),22 30 39–47 2 narrative reviews,48 49 2 rapid reviews,50 51 1 umbrella review,52 1 mini-review53 and 1 systematic review of systematic reviews 54. The majority of the reviews aimed to explore the effectiveness of several or all of the digital interventions on reducing loneliness 31 35 36 39 40 45 47–49 52 53.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation